2017
DOI: 10.1038/tp.2016.267
|View full text |Cite
|
Sign up to set email alerts
|

Brain volumetric and metabolic correlates of electroconvulsive therapy for treatment-resistant depression: a longitudinal neuroimaging study

Abstract: Recent research suggests that neuroplastic and neuroinflammatory changes may account for the mode of action of electroconvulsive therapy (ECT), although extant data do not allow for a clear disambiguation between these two hypotheses. Multimodal neuroimaging approaches (for example, combining structural and metabolic information) may help in clarifying this issue. Here we aimed to assess longitudinal changes in (i) regional gray matter (GM) volumes and (ii) hippocampal metabolite concentrations throughout an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 60 publications
10
66
1
Order By: Relevance
“…In general, an overall increase in HV was seen in our sample following ECT, which was over an average period of 54 days. This is in line with other studies reporting an ECT‐induced increase in HV in depressed patients compared to depressed patients without ECT and healthy controls , during the same time window. The increase must be interpreted with caution since random variation and measurement errors could be a cause of the change in HV over time.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In general, an overall increase in HV was seen in our sample following ECT, which was over an average period of 54 days. This is in line with other studies reporting an ECT‐induced increase in HV in depressed patients compared to depressed patients without ECT and healthy controls , during the same time window. The increase must be interpreted with caution since random variation and measurement errors could be a cause of the change in HV over time.…”
Section: Discussionsupporting
confidence: 93%
“…Electroconvulsive seizures (ECS), the animal model of ECT, indicates that increased neuroplasticity in the dentate gyrus , might be responsible for the observed changes in HV. Also, several preclinical studies suggest that increased neuroplasticity in the hippocampus causes memory impairments , , .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior cingulate cortex (ACC) has an anatomical connection with dorsal neocortical and ventral paralimbic regions and plays a role in cognitive processes and mood regulation . The right anterior cingulate cortex was reported to have a decreased magnetization transfer ratio in patients with treatment‐refractory MDD relative to healthy controls, which increased after electroconvulsive therapy . Previous studies have also found that prefrontal areas undergo a significant reduction in thickness, and these changes are thought to be associated with poor clinical outcomes .…”
Section: Significant Structural Brain Alterations In Mddmentioning
confidence: 98%
“…27 The right anterior cingulate cortex was reported to have a decreased magnetization transfer ratio in patients with treatment-refractory MDD relative to healthy controls, 28 which increased after electroconvulsive therapy. 29 Previous studies have also found that prefrontal areas undergo a significant reduction in thickness, 4,[30][31][32] and these changes are thought to be associated with poor clinical outcomes. 33 A negative correlation was observed between the Montgomery-Asberg Depression Rating Scale score and cortical thickness in the ACC.…”
Section: Frontal Lobementioning
confidence: 98%